Community Service-Learning in Canada: Emerging Conversations (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2018)
This special issue invites engaged learning practitioners and scholars, both established and emerging, to take stock of the history of CSL, assess current practices, and consider how to move forward in the future. Is CSL the biggest thing to hit Canadian campuses since the late 1990s? With approximately fifty CSL programs or units across the country (Dorow et al., 2013), annual gatherings of scholars and practitioners, and a network of individuals who remain devoted to CSL despite challenges in funding and logistics, CSL in Canada has certainly made its mark, embedded in the context of a larger movement of engaged scholarship on campuses across the country—a movement exemplified in this very Engaged Scholar Journal, the first of its kind in Canada to focus on publishing community-engaged work.